The remediation challenge: theoretical and methodological insights from a systematic review. Issue 3 (8th February 2013) - Cleland, Jennifer; Leggett, Heather; Sandars, John; Costa, Manuel J; Patel, Rakesh; Moffat, Mandy
<x xml:space="preserve">Abstract</x> Objectives Remediation is usually offered to medical students and doctors in training who underperform on written or clinical examinations. However, there is uncertainty and conflicting evidence about the effectiveness of remediation. The aim of this systematic review was to synthesise the available evidence to clarify how and why remediation interventions may have worked in order to progress knowledge on this topic. Methods The MEDLINE, EMBASE, CINAHL (Cumulative Index to Nursing and Allied Health Literature), ERIC (Educational Resources Information Centre), Web of Science and Scopus databases were searched for papers published from 1984 to April 2012, using the search terms 'remedial teaching', 'education', 'medical', 'undergraduate'/or 'clinical clerkship'/or 'internship and residency', 'at risk' and 'struggling'. Only studies that included an intervention, then provided retest data, and reported at least one outcome measure of satisfaction, knowledge, skills or effects on patients were eligible for inclusion. Studies of practising doctors were excluded. Data were abstracted independently in duplicate for all items. Coding differences were resolved through discussion. Results Thirty‐one of 2113 studies met the review criteria. Most studies were published after 2000 (n = 24, of which 12 were published from 2009 onwards), targeted medical students (n = 22) and were designed to improve performance on an immediately subsequent examination (n = 22). Control or comparison groups, conceptual frameworks, adequate sample sizes and long‐term follow‐up measures were rare. In studies that included long‐term follow‐up, improvements were not sustained. Intervention designs tended to be highly complex, but their design or reporting did not enable the identification of the active components of the remedial process. Conclusions Most remediation interventions in medical education focus on improving performance to pass a re‐sit of an examination or assessment and provide no insight into what types of extra support work, or how much extra teaching is critical, in terms of developing learning. More recent studies are generally of better quality. Rigorous approaches to developing and evaluating remediation interventions are required.